Antifungal efficacy of Ocimum Basilicum essential oil in tissue conditioner against Candida Albicans: An In vitro study - Aiemeeza Rajali; Nurhayati Mohamad Zain; Nurafiqah Aina Amran; Nurin Hazirah Enche Muhammad Azmi (Wolters Kluwer Medknow Publications, 2023)
Tissue conditioner is used to condition inflamed mucosa induced by denture stomatitis. However, the drawback of the aging tissue conditioner is increased surface roughness, thus enhance microbial adhesion. Ocimum basilicum is known for its antimicrobial effects but its use in liners has not been investigated. Aims: This study aimed to determine the antifungal efficacy of ocimum basilicum essential oil (OBEO) when incorporated into tissue conditioner against C. albicans and the effect on the properties. Subject and Methods: The antimicrobial activities were determined using disc diffusion, minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). After incorporation into tissue conditioner, the color difference and surface roughness were evaluated after one day. The surface morphology and the antibiofilm activity were assessed on day 1 and day 14. Results: The zone of inhibition of OBEO on Sabouraud Dextrose agar was significantly wider than nystatin and deionized water (P=0.000) with the MIC and MFC values were 1.25% and 5%. Both OBEO concentrations incorporated into tissue conditioner, there was no significant difference of color changes in the light-dark character (P=0.102) and surface roughness (P=0.920) when compared to the control group. As for adherence at days 1 and 14, both concentrations of OBEO in tissue conditioner show significantly reduced adherence of C. albicans compared to the control group (P=0.000). Conclusion: OBEO exhibited significantly better antifungal activity against C. albicans when compared to nystatin and deionized water and resulted in no significant color changes, better surface roughness and lesser adherence of C. albicans toward the tissue conditioner.